PENGARUH DAUN JAMBU BIJI SEBAGAI INHIBITOR KOROSI ALAMI RANTAI KAPAL - Nani Mulyaningsih; Sigit Mujiarto; Gyani Ubaydillah (Universitas Tidar, 2019)
Corrosion is the interaction of metals with their environment which results in damage to metals. Corrosion can also occur in the chain of vessels that are usually located on the side of the ship's hull and are directly exposed to sea water. If it is not properly observed, the condition will damage and reduce the life of the ship chain. It is necessary to add inhibitors as substances to inhibit the corrosion rate. Inhibitors that are generally used are inhibitors that have toxic properties to the environment, therefore it is necessary to use organic inhibitors that do not damage the environment. The purpose of this study was to determine the effect of inhibitors of guava leaf extract on the corrosion rate of ship chains. This research was conducted by immersing specimens with concentrations of 6%, 9%, 12%, and immersion time of 1 hour. Corrosion rate is calculated using the dynamic potentiary polarization method. After calculating the corrosion rate, the inhibitor efficiency is calculated. After immersion is obtained, the inhibitor has an influence. This was shown after the corrosion test found that at a concentration of 9% inhibitors of guava leaf extract was able to reduce the corrosion rate of 0.066 mpy and has the highest efficiency value of 97.3%.